2021
DOI: 10.15252/embr.202051847
|View full text |Cite
|
Sign up to set email alerts
|

CK1‐mediated phosphorylation of FAM110A promotes its interaction with mitotic spindle and controls chromosomal alignment

Abstract: Progression through the cell cycle is driven by cyclin-dependent kinases that control gene expression, orchestration of mitotic spindle, and cell division. To identify new regulators of the cell cycle, we performed transcriptomic analysis of human nontransformed cells expressing a fluorescent ubiquitination-based cell cycle indicator and identified 701 transcripts differentially expressed in G1 and G2 cells. Family with sequence similarity 110 member A (FAM110A) protein is highly expressed in G2 cells and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…1 B ). Interestingly, AlphaFold2 showed that interaction of tubulin could potentially be mediated by a conserved alpha-helix comprising residues 188–221 of FAM110A that are close to the previously reported phosphorylated sites promoting the binding of FAM110A to the spindle poles ( 20 ) ( Fig. 1 C ).…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…1 B ). Interestingly, AlphaFold2 showed that interaction of tubulin could potentially be mediated by a conserved alpha-helix comprising residues 188–221 of FAM110A that are close to the previously reported phosphorylated sites promoting the binding of FAM110A to the spindle poles ( 20 ) ( Fig. 1 C ).…”
Section: Resultsmentioning
confidence: 54%
“…In our previous work, we showed that FAM110A interacts with tubulin and actin during mitosis ( 20 ). Here, we aimed to map and functionally characterize the interaction of FAM110A with both cytoskeletal systems.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, it was demonstrated that CK1 interacts with FAM110A during mitosis, and inhibition of CK1 or depletion of FAM110A, led to chromosomal alignment defects and delayed mitosis progression ( Figure 3 ). Interestingly, defects in chromosomal alignment were rescued by mimicking phosphorylation with FAM110A-S252-255E mutants [ 68 ]. Functional binding partners of CK1, such as the anchoring proteins FAM83 and FAM110A, could be used as alternative targets in cancer treatment by blocking specifically the interaction of CK1 isoforms with these anchoring proteins and thus, inhibiting CK1 isoform-mediated substrate phosphorylation (see also Section 7.4 ) [ 68 ].…”
Section: The Role Of Ck1 In Cell Cycle Progressionmentioning
confidence: 99%